O entrecruzamento do pensamento de Jonathan Edwards e Francis Schaeffer no envolvimento apologético reformado - Bezerra, Samuel Santos (2019)
The present work proposes an intersection between the thoughts of Jonathan Edwards and Francis Schaeffer as a bridge to rethink the apologetic exercise which comprehends itself in the spectrum of personal involvement, which sees the other not as an opposer or enemy, but as a human being in need of God’s grace and which visualizes him in its broadest dimension, involving reason and affection. The subject is understood as a relevance acquirer in a context marked by polarization in several areas. Such tendency does not exclude the discussion interface as it has been presented nowadays, having, on one hand, the attempt of maximizing the reason by neglecting other faculties of the human constitution, and, on the other hand, the embrace of the relativism, renouncing the categories of the absolute, trying to survive in the field of sensation. The reformed apologetic exercise will have bigger difficulties if it does not understand, in this environment, the other with whom one dialogues and how to dialogue. The intersection of the mentioned authors is to be brought to light in order to rethink the essential aspects of apologetic development, seeing them expressed in the dialogical process marked by the credentials of the truth in love.